Study on the optical and biological properties in vitro of IR808‐PEG‐FA. Issue 9 (18th April 2020) - Wang, Sujun; Tang, Qianqian; Ya, Huiyuan; Fan, Yanli; Feng, Wenjing; Du, Jie; Fang, Shengtao; Shi, Chunmeng
Abstract: IR808, an IR780 derivative, is capable of fluorescently imaging and photodynamic therapy in vitro and in vivo. However, its application is greatly hampered by hydrophobicity, toxicity and nonspecific delivery to the targeting tissue and that causes accumulation in the liver and kidney. In order to overcome these limitations, we prepared IR808‐PEG‐FA from IR808, amino‐terminated poly(ethylene glycol) (NH2 ‐PEG‐NH2, denoted as PEG) and folate (FA). PEG, an accepted hydrophilic medicinal agent, was introduced to improve hydrophobicity, and FA was used to increase targeting ability of the conjugate. The obtained product provides a good water solubility and stronger light intensity in near infrared (NIR)‐imaging, and CCK‐8 test demonstrated which had no appreciable toxicity. In addition, the cell uptake results indicated that IR808‐PEG‐FA was specifically targeted to positive tumors cells with folate receptor (FR) compared with IR808, and thus it may be used as a novel diagnostic agent or imaging‐guided agent for cancer treatment. So this article provides a way to improve hydrophobicity, optical stability and targeting ability in the field of nano‐probe for fluorochromes.